Geozoological characteristics of the ichthyofauna of the water bodies of the Kuban river basin (based on the materials of the Karachay-Cherkess Republic) - A. Z. Kerefov; Yu. P. Kostin; R. S. Gubanov (Наука. Инновации. Технологии)
The article studies geozoological characteristics of the mountain rivers of the Kuban River basin within the borders of the KarachayCherkess Republic. The water availability of the Karachay-Cherkess Republic stands out from other southern regions of the Russian Federation with a significantly wide network of rivers. There are 419 rivers flowing through the territory of the republic, belonging to two basins: the Azov-Black Sea and the Caspian, and there are also over 130 lakes. All the rivers of the Azov-Black Sea basin are tributaries of various orders of the Kuban River. The largest tributaries of the first order are the rivers: Teberda, Maly Zelenchuk and Bolshoy Zelenchuk, Urup, Laba [4]. Currently, the rivers of the Kuban River basin are well-studied water bodies, however, due to the considerable length of the rivers, their upper reaches have been poorly studied. This is due to the fact that most ichthyological studies are aimed at studying the transformation of the ichthyofauna and the food supply, in connection with the construction of hydraulic structures: reservoirs, canals, hydroelectric power plants, etc. or studying the reduction of populations of sturgeon fish, due to the lack of migration routes. The purpose of this study is to study the ichthyofauna, food supply and habitat of the Upper Kuban and the upper reaches of the tributary river. The object of the study is the hydrobionts of the mountain rivers of the Karachay-Cherkess Republic. During the hydrobiological field research, generally accepted research methods were used. The identification of the fish species was carried out according to the appropriate determinants (Atlas, 2003; Berg, 1948-1949; Kuznetsov, 1973; Veselov, 1977; Kottelat, Freyhof, 2007, etc.), according to the modern classification (Reshetnikov et al., 1997; Reshetnikov et al, 2003; Shakhmurzov et al, 2012; Kottelat, Freyhof, 2007). The collection of aquatic invertebrates was carried out using generally accepted hydrobiological methods (Lipin, 1950; Martynov, 1952; Lepneva, 1968; Lukin, 1976; Fomin, 2000; Tsalolikhin, 1994–2004, etc.). The main result of the work was the compilation of geozoological characteristics of the ichthyofauna of the upper reaches of the Kuban River. Studies of the rivers of the upper reaches of the Kuban River confirm that the ichthyofauna is represented almost exclusively by brook trout.